Implementing experiential STEAM projects based on 3D modeling and printing to enhance teachers' techno-pedagogical competencies - Putranto, Dedy; Juliansyah, Ari; Saputra, Adi; Rahmadi, Imam Fitri (Community Empowerment, 2026)
Learning with an experiential Science, Technology, Engineering, Arts, and Mathematics (STEAM) approach has the potential to foster deeper learning processes. However, elementary school teachers generally remain unfamiliar with supporting technologies such as 3D modeling and printing. This community service program aims to enhance teachers' capacity to integrate these technologies into the curriculum. Utilizing a teacher-researcher partnership framework, the program was implemented in five stages: socialization, technical training, technology implementation, mentoring, and evaluation. The evaluation results showed a significant increase in software modeling familiarity, rising from only 4% of teachers (1 person) to 100% of teachers mastering the technical aspects. Although there was a general improvement in pedagogical capabilities, a decrease in understanding was observed regarding complex object components and technical limitations of the equipment. This emphasizes that short-term training must be supported by continuous mentoring to stabilize technology adoption. This program successfully built teachers' confidence in designing interdisciplinary learning innovations relevant to Industry 4.0 requirements.